Diagnosis of Peripheral Facial Palsy Associated with Parvovirus B19 Infection by Polymerase Chain Reaction - Taro Fukuta; Yoshihiko Kawano; Maiko Ikeda; Jun-ichi Kawada; Yoshinori Ito; Shinya Hara (Case Reports in Pediatrics)
Human parvovirus B19 (PVB19) infection causes neurological manifestations, including encephalitis, meningitis, and neuropathy, but facial nerve palsy is rare. Moreover, no case of facial nerve palsy related to PVB19 infection that was diagnosed by PCR and serology has been reported. A 19-month-old boy without the medical history developed facial nerve palsy and was treated with prednisolone and valacyclovir. On the 19th day, erythema appeared on his body, and the PVB19-specific IgM and PVB19 DNA were detected in the serum, leading to the diagnosis of infectious erythema associated with PVB19 infection. This case indicates that PVB19 may be one of the causative agents of facial nerve palsy.